2019
DOI: 10.1002/1878-0261.12571
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNAs involved in pathways which characterize the expression subtypes of NSCLC

Abstract: Dysregulation of microRNAs is a common mechanism in the development of lung cancer, but the relationship between microRNAs and expression subtypes in non‐small‐cell lung cancer (NSCLC) is poorly explored. Here, we analyzed microRNA expression from 241 NSCLC samples and correlated this with the expression subtypes of adenocarcinomas (AD) and squamous cell carcinomas (SCC) to identify microRNAs specific for each subtype. Gene set variation analysis and the hallmark gene set were utilized to calculate gene set sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…To explore differences in potential biological processes in CC patients from different clusters, GSEA was performed using the hallmark gene sets (h.all.v7.0.symbols), which were obtained from the Molecular Signatures Database (https://www.gsea-msigdb.org/gsea/ msigdb/index.jsp). The hallmark gene sets display coordinate expression and represent well-defined biological processes, providing a clearer biological space for GSEA (Halvorsen et al, 2019;Liberzon et al, 2015). The 'fgsea' R package was used, and 10 000 permutations were performed for each parameter analyzed to calculate the enrichment scores based on the threshold of adjusted P-value < 0.05 (Sergushichev, 2016).…”
Section: Gene Set Enrichment Analysis (Gsea)mentioning
confidence: 99%
“…To explore differences in potential biological processes in CC patients from different clusters, GSEA was performed using the hallmark gene sets (h.all.v7.0.symbols), which were obtained from the Molecular Signatures Database (https://www.gsea-msigdb.org/gsea/ msigdb/index.jsp). The hallmark gene sets display coordinate expression and represent well-defined biological processes, providing a clearer biological space for GSEA (Halvorsen et al, 2019;Liberzon et al, 2015). The 'fgsea' R package was used, and 10 000 permutations were performed for each parameter analyzed to calculate the enrichment scores based on the threshold of adjusted P-value < 0.05 (Sergushichev, 2016).…”
Section: Gene Set Enrichment Analysis (Gsea)mentioning
confidence: 99%
“…It has been reported that lung adenocarcinoma subtypes have different metabolism profiles [33,34]. Our group previously demonstrated that the PI group has the highest tumor metabolism index, which is a deeplearning-based index used to predict SUVmax from transcriptomic data among the three subtypes [12].…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, since miR-140-3p is highly expressed by B cells, low levels of miR-140-3p may indicate the absence of B cell infiltration. [ 25 ] JAK-STAT inhibition has been recently shown to impair K-RAS-driven lung adenocarcinoma progression and is a promising therapy for K-RAS-driven lung LUAC. [ 26 ] Finally, miR-140-3p overexpression was found to attenuate cisplatin resistance and reduce stem cell-like properties in LUAD cells by suppressing Wnt/β-catenin signaling.…”
Section: Discussionmentioning
confidence: 99%